Interactions between Jews and Christians in Later Medieval Provence - Smail, Daniel Lord (Medieval encounters, 2021)
This study uses an extensive body of archival evidence from Latin-Christian sources to explore economic and social interactions between Provençal Jews and Christians. Evidence discussed in section one indicates that the city’s Jewish and Christian communities interacted to a significant degree, and not just in the domain of moneylending. Data derived from a network analysis suggests that Jews were prominent in providing brokerage services. In the second section, analysis of a small sample of Jewish estate inventories indicates that the material profiles of Jewish and Christian families were very similar. In the third section, an analysis of a register of debt collection shows that Jews were involved in credit relations at a rate that was proportional to their population. Jewish moneylenders filled an economic niche by providing Christians with the liquidity to pay off structural debts generated by the political economy of rents and taxes.